Prosthetic valve endocarditis due to Candida parapsilosis – a rare case report. Issue 1 (24th January 2023) - Sharma, Shivang; Samantaray, Subhashree; Kumar, Deepak; Meena, Durga Shankar; Chaudhary, Rahul; Jain, Vidhi; Bohra, Gopal Krishana; Garg, Mahendra Kumar
Abstract : Fungal endocarditis is a rare and fatal condition, most frequently caused by species of the genera Candida and Aspergillus . Fever and changing heart murmur are the most common clinical manifestations. The diagnosis of fungal endocarditis is challenging, with prosthetic valve endocarditis being extremely difficult to diagnose. The optimal management of the condition still remains debatable. We present a case of prosthetic valve endocarditis caused by Candida parapsilosis, managed empirically with liposomal amphotericin B, which was later shifted to combination therapy with high-dose echinocandin and fluconazole, but had a fatal outcome because the patient could not undergo timely surgical intervention. Treating C. parapsilosis endocarditis cases is difficult because of their biofilm production on native and prosthetic heart valves. A combined approach consisting of a high index of clinical suspicion, early diagnosis using serological markers followed by culture or PCR and prompt initiation of appropriate antifungals may aid in improving outcomes.